Workshop on best practice methods for assessing the impact of policy-oriented research: Summary and recommendations for the CGIAR - Place, Frank; Hazell, Peter B. R. (International Food Policy Research Institute, 2015)
There is a low number of studies on the impact of policy oriented research (PORIA) and an even lower number of those that undertake a quantitative assessment of impacts. In comparison, there are numerous quantitative impact assessment studies of technology research, thus creating an imbalance of evidence for decisionmakers interested in investing in agricultural research. There are many reasons for this, but one has been the challenges in PORIA, notably in methods to assess attribution of policy outcomes to research and the measurement of impacts of policy outcomes. To respond to this, a workshop was convened from November 12-14, 2014 at IFPRI headquarters in Washington, DC. It was cosponsored by IFPRI; the CGIAR Research Program on Policies, Institutions, and Markets (PIM); and the Standing Panel on Impact Assessment (SPIA) of the CGIAR’s Independent Science and Partnership Council (ISPC).